The Implementation of Tri Hita Karana Value and Strategy Based on Social Capital in Creating Competitive Advantages in Village Credit Institutions in the Penglatan Village - Gusti Putu Eka Kusuma (Universitas Pendidikan Ganesha, 2020)
Companies that are able to implement strategies that are oriented more to the external environment will be able to develop market share well and more quickly in anticipating changes that occur suddenly, thus the company is declared to have an effective strategy in the sense that it will be able to compete. This research conducted at the Village Credit Institutions in Penglatan collected through interviews. Research informants were 3 people through purposive sampling. This research was tested using interactive models. The results showed that the application of the tri hita karana value and the application of a social capital-based strategy made the village credit institution Penglatan able to build trust in the village krame where the value of the tri hita karana namely pawongan (human relations with humans) and awig - awig became the basis for the operational implementation of credit institutions villages can increase trust and build competitive advantage